Monitoring Driver Distraction in Real Time using Computer Vision System - Kulkarni, AS; Shinde, SB (International Journal of Computer Sciences and Engineering, 2025)
Driver tiredness is one of the most important causes of road accidents. This article presents a real-time non disturbance drowsiness monitoring scheme which exploits the driver’s facial appearance to identify and aware tired drivers. This presented work worn the Viola-Jones Algorithm to identify the driver’s facial appearance. Continuously Adaptive Mean Shift algorithm has been used for continuous face tracing of driver. With this uncomplicated and not expensive execution, the whole scheme achieved an accuracy of 99.5%, outperforming other developed schemes adopting expensive hardware to arrive at the similar objective.